(untitled) (Revista de Estudos da Linguagem, 2019)
Abstract: This paper investigates the empirical properties of morphologically complex verbs of change in Brazilian Portuguese. Its main goal is to find out whether there are (not) correlations between prefix morphophonological form, root semantics and verb argument structure. All verbs analyzed denote events in which the internal argument is the undergoer of a change, and a classification in four semantic subclasses according to their root meaning is proposed: state, place, transfer of possession (either abstract or concrete) and reconfiguration. Contrary to what previous literature has suggested, fine-grained investigation within each of these classes has shown that it is not possible to exclusively associate morphological forms to specific root semantics or morphosyntactic behavior, although it is possible to observe general tendencies. To provide an analysis to account for the robust homogenous structural properties and general semantics behavior across the class, in face of the morphological variation in what regards prefix choice among the forms a-, en- and es-, it is proposed that prefixes are the phonological realizations of a functional head in the lower domain of the verb (labeled R, Relational) whose choice is given in terms of contextual allomorphy. It is shown that vocabulary insertion at R is guided by locality with the root. The theory of allomorphy proposed in Embick (2010), which is based on locality and linearity, was efficient in accounting for the selection of allomorphs of R, v and Th (Theme Vowel) heads. Keywords: complex verbs; prefixes; allomorphy; Brazilian Portuguese; Distributed Morphology. Resumo: Esse artigo investiga as propriedades empíricas de verbos de mudança morfologicamente complexos do português brasileiro. Seu objetivo principal é descobrir se há ou não correlações entre a forma morfofonológica do prefixo, a semântica da raiz e a estrutura argumental do verbo. Todos verbos analisados denotam eventos em que o argumento interno é o objeto afetado de uma mudança, e uma classificação em quatro subclasses semânticas de acordo com o significado atribuído à raiz é proposta: estado, lugar, transferência de posse (abstrata ou concreta), e reconfiguração. Contrariamente ao que foi sugerido pela literatura anterior, a investigação detalhada dentro de cada uma dessas classes mostrou que não é possível associar exclusivamente as formas morfológicas prefixais à semântica específica da raiz ou ao comportamento morfossintático do verbo, embora seja possível observar tendências gerais. Para fornecer uma análise para explicar as robustas e homogêneas propriedades estruturais e o comportamento semântico geral em toda a classe em face da variação morfológica em relação à escolha do prefixo entre as formas a-, en- e es-, propõe-se que os prefixos sejam realizações fonológicas de um núcleo funcional no domínio baixo do verbo (rotulado como R, de Relacional) cuja escolha é dada em termos de alomorfia contextual. Mostra-se que a inserção de vocabulário em R é orientada por localidade com a raiz. A teoria de alomorfia prospota em Embick (2010), baseada em localidade e linearidade, se mostra efetiva para analisar a escolha dos alomorfes dos núcleos R (relacionador), v e Th (Vogal temática). Palavras-chave: verbos complexos; prefixos; alomorfia; português brasileiro; Morfologia Distribuída.